Implementation of Moral Education in Adolescents - Dian Shintia Afrina; Afrahamiryano, Afrahamiryano (Elementaria: Journal of Educational Research, 2024)
Moral education plays a vital role in shaping the character and maturity of students, especially during adolescence which is a critical development period. This research uses literature study methods to analyze various aspects of moral education, including the importance of instilling moral values ​​from an early age, the role of family and school, as well as the impact of technology and mass media. The research results show that the moral development of adolescents is greatly influenced by the environment and the people around them. Teachers and parents play a key role in providing consistent and effective guidance to support adolescents' moral development. It is hoped that the implementation of a curriculum that emphasizes moral development, as well as quality planning and programs in schools, can form a generation with good morals, noble character and social responsibility.